2004
DOI: 10.1111/j.1471-4159.2004.02875.x
|View full text |Cite
|
Sign up to set email alerts
|

Vlgr1 knockout mice show audiogenic seizure susceptibility

Abstract: Susceptibility to audiogenic seizures, which are reflex seizures provoked by loud noise, can be induced in rodents by acoustic priming (exposing animals to strong auditory stimuli at an early developmental stage). Some strains of mice and rats are susceptible to audiogenic seizures without priming and these have been used as good experimental models with which to study epilepsies. Here we identified Vlgr1d and Vlgr1e, novel alternatively-spliced variants of Vlgr1b/MGR1, which, upon sequence analysis, were show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…14), WHRN may prefer to bind to USH2A in photoreceptors. Interestingly, weak and late onset retinal degeneration has been found in Ush2a Ϫ/Ϫ and Whrn neo/neo mice (21,22), whereas no retinal degeneration has been reported in various Gpr98 mutant mice (10,11,16,(41)(42)(43)(44)(45). Therefore, USH2A and WHRN might have more dominant roles than GPR98 and PDZD7 in photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…14), WHRN may prefer to bind to USH2A in photoreceptors. Interestingly, weak and late onset retinal degeneration has been found in Ush2a Ϫ/Ϫ and Whrn neo/neo mice (21,22), whereas no retinal degeneration has been reported in various Gpr98 mutant mice (10,11,16,(41)(42)(43)(44)(45). Therefore, USH2A and WHRN might have more dominant roles than GPR98 and PDZD7 in photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…22 GPR98/MASS1 knockout mice show audiogenic seizure susceptibility. 23 Loss of function mutations of GPR98/MASS1 have been demonstrated in an autosomal-dominant family with familial febrile seizures. 24 All affected family members had normal mental and motor development and a brain MRI showed no abnormal findings.…”
Section: Discussionmentioning
confidence: 99%
“…Frings mice carry a spontaneous mutation of Mass1 ( Mass1 Frings ) that also results in mutation of Vlgr1b (McMillan et al 2002). Then, we and other groups observed that Vlgr1 (Vlgr1b, Vlgr1c, Vlgr1d, Vlgr1e) knockout mice and mice with mutated Vlgr1 show high susceptibility to audiogenic seizures (Skradski et al 2001;Yagi et al 2003Yagi et al , 2005McMillan & White 2004). Recently, cochlear abnormalities were reported in BUB/BnJ mice, which carry a Mass1…”
Section: Introductionmentioning
confidence: 96%
“…Vlgr1b, whose mRNA is approximately 19 kb in size, is one of the G-protein coupled receptors with a huge extracellular domain in which there are many Calx-β domains, potential calcium binding domains, as inferred from the deduced amino acid sequence. We identified two alternative splicing variants, Vlgr1d and Vlgr1e, and made Vlgr1 knockout mice that lost the functional products of Vlgr1b, Vlgr1d, Vlgr1e and Vlgr1c, which is another alternative splicing variant of Vlgr1 (McMillan et al 2002;Yagi et al 2005). Mass1, which is one of the Vlgr1 alternative splicing variants, was reported to be the gene responsible for the susceptibility to audiogenic seizure of Frings mice (Skradski et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation